Midazolam pharmacokinetics in obese and non-obese children and adolescents - Gade, Christina; Sverrisdóttir, Eva; Dalhoff, Kim; Sonne, Jesper; Johansen, Mia Østergaard; Christensen, Hanne Rolighed; Burhenne, Jürgen; Mikus, Gerd; Holm, Jens Christian; Lund, Trine Meldgaard; Holst, Helle (Clinical pharmacokinetics, 2020)
Midazolam is a first-line drug for the treatment of status epilepticus, both by buccal and intravenous administration. In children and adolescents with obesity, midazolam pharmacokinetics may be altered, and the current dosing guidelines may therefore be insufficient.
Published online: 19 November 2019
Gesehen am 08.06.2020